2008
DOI: 10.1309/9m7dfe62rtdkhh4d
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies Between Clinical and Autopsy Diagnoses

Abstract: Although it is known that autopsies often disclose unexpected findings, few studies have been published that address the effect of institutional setting, selection bias, and length of hospitalization. Records of medical autopsies from 3 institutional settings were studied for discrepancies between clinical and autopsy findings. The settings were university hospital (n = 85); community hospital (n = 146); and private autopsy (n = 60), which were referred from various community hospitals and paid for by family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…This is consistent with a report by Friedlander in England who reported more than a quarter of autopsies resulting to major surprises other than the said antemortem cause of death [6]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with a report by Friedlander in England who reported more than a quarter of autopsies resulting to major surprises other than the said antemortem cause of death [6]. …”
Section: Discussionsupporting
confidence: 92%
“…This calls for the need to request for autopsies for medical auditing to sharpen clinical acumen. Friedlander reported that autopsy results have been able to aid by obtaining confirmative diagnosis of patients [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Antemortem medical and forensic information should be evaluated jointly [29, 30]. The range of events presented in our study is sufficient to demonstrate the variety of cases.…”
Section: Discussionmentioning
confidence: 98%
“…Depending on the severity of the trauma, and thus on the time available for establishing the diagnosis, the use of diagnostic means may be very limited. Yet, a recent study points out that the in-hospital survival time is inversely proportional to the discrepancy rate at autopsy, suggesting that lack of time for appropriate diagnostic tests have an important role in missed diagnoses [18]. Especially in fatal polytrauma cases the clinically assumed causes of death might vary from the autopsy point of view, depending on several factors such as the patient's pre-existing condition and age, mechanism of accident, necessity of CPR, survival time, and the possibility to perform emergency diagnostics: if severe injury patterns with elevated ISS levels necessitate continued CPR on the patient in immediate clinical course, intended advanced diagnostic measures (besides standardly conducted performance of physical body exploration, thoracic and pelvic x-ray scans as well as abdominal ultrasound examination) usually will initially be blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Yet current literature has documented a decrease in autopsy frequency; the reasons are diversified, including technological advances in clinical testing and imaging and apprehension of potential medicolegal consequences resulting from discrepant findings. Nevertheless, disparity rates between clinical and post-mortem diagnoses concerning the cause of death are reported to reach up to 17.2% [18]. …”
Section: Discussionmentioning
confidence: 99%